Wild about Books - Sierra, Judy; Brown, Marc Tolon (New York : Knopf, 2004)
A librarian named Molly McGrew introduces the animals in the zoo to the joy of reading when she drives her bookmobile to the zoo by mistake.
Accelerated Reader AR